PENGEMBANGAN BAHAN AJAR E-COMIC CREATOR MATERI KEKAYAAN BUDAYA INDONESIA BERBANTUAN APLIKASI PIXTON - Aisyah Fitriana M; Resyi A. Gani; Nur Hikmah (STKIP Subang, 2025)
Development of E-Comic Creator Teaching Materials on Indonesian Cultural Wealth Material Assisted by Pixton Application. The type of research used is the Research and Development (R&D) approach at Elementary School 02 Cogreg on grade IV students with a research model, namely the ADDIE method (Analysis, Design, Development, Implementation and Evaluation). This research began with conducting needs analysis, curriculum analysis, student analysis, and product design. Furthermore, e-comic teaching materials were developed using the pixton application, which were then validated by experts. After that, a trial was conducted on e-comic teaching materials using the pixton application on Indonesian cultural wealth material to the respondents who had been determined. The validation results from media experts, material experts, and language experts showed that e-comic teaching materials using the pixton application were considered very valid and very feasible to use, with an average percentage of 97%. In the trial phase, as many as 25 students were involved as respondents and gave very positive responses to the teaching materials used with an average percentage reaching 90%. Based on the results of this study, it can be concluded that the e-comic teaching materials assisted by the pixton application on the material on Indonesian cultural wealth are valid, interesting, easy to use by students, and are used as a source of teaching materials in learning activities.